Pengaruh Human And Social Board Capital Dan Kinerja Lingkungan Terhadap Sustainability Reporting Pada Perusahaan Sektor Energi Yang Terdaftar Di Bursa Efek Indonesia (BEI) - Wiwi Allawiyah; Citra Indah Merina (JURNAL ILMIAH EDUNOMIKA, 2025)
Sustainability issues have become a major concern for companies, particularly in the energy sector which carries significant social and environmental risks. Companies are required to prepare sustainability reports that are transparent and accountable in accordance with global standards as well as national regulations such as POJK No. 51/POJK.03/2017. However, the practice of sustainability reporting in Indonesia still faces several challenges, including discrepancies between reports and operational conditions, as well as indications of greenwashing that undermine the credibility of disclosures. This study aims to examine the influence of Human and Social Board Capital (HSBC) and environmental performance on sustainability reporting in energy sector companies listed on the Indonesia Stock Exchange (IDX). The research data were obtained from annual reports and sustainability reports of 35 companies during the 2021–2023 period. A quantitative approach with multiple linear regression analysis was employed. This study is expected to provide theoretical contributions to the development ofsustainability reporting literature as well as practical implications for companies in improving transparency, governance quality, and accountability in sustainability disclosures.Keywords : Human and Social Board Capital, Environmental Performance, Sustainability Reporting, Energy Companies